2023
DOI: 10.1038/s41467-023-40986-4
|View full text |Cite
|
Sign up to set email alerts
|

Lrig1-expression confers suppressive function to CD4+ cells and is essential for averting autoimmunity via the Smad2/3/Foxp3 axis

Jae-Seung Moon,
Chun-Chang Ho,
Jong-Hyun Park
et al.

Abstract: Regulatory T cells (Treg) are CD4+ T cells with immune-suppressive function, which is defined by Foxp3 expression. However, the molecular determinants defining the suppressive population of T cells have yet to be discovered. Here we report that the cell surface protein Lrig1 is enriched in suppressive T cells and controls their suppressive behaviors. Within CD4+ T cells, Treg cells express the highest levels of Lrig1, and the expression level is further increasing with activation. The Lrig1+ subpopulation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…For example, Guimenny et al, used non-neuronal cell lines and C.elegans to discover both direct and genetic interactions between BMPR’s and LRIG1 via a series of immunoprecipitation assays 21 and animal physiology. Additionally, Ferguson et al demonstrated dysregulation in BMP signalling as assessed by SMAD expression via immunostaining and western blotting in a Lrig1 KO glioblastoma cell line and others have begun exploring the TGF β superfamily and LRIG1 in other cell types 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Guimenny et al, used non-neuronal cell lines and C.elegans to discover both direct and genetic interactions between BMPR’s and LRIG1 via a series of immunoprecipitation assays 21 and animal physiology. Additionally, Ferguson et al demonstrated dysregulation in BMP signalling as assessed by SMAD expression via immunostaining and western blotting in a Lrig1 KO glioblastoma cell line and others have begun exploring the TGF β superfamily and LRIG1 in other cell types 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%